Meningkatkan Keterampilan Membaca Teks Berita melalui Metode STAD (Student Teams Achievement Division) pada Siswa Kelas XI SMA Negeri 3 Bone : Improving News Text Reading Skills Through the STAD (Student Teams Achievement Division) Method in Class XI Students of SMA Negeri 3 Bone - Dewi Gita; Muin, Nurmiah; Mansyur, Umar (ITScience (Information Technology and Science), 2024)
Indonesian language learning at all levels of education is to provide teaching or guidance for students to be able to apply Indonesian in various aspects. One of the basic competencies taught in Senior High Schools, especially for grade XI students and related to reading skills, is reading news texts briefly, concisely, and clearly. Learning to read news texts is in line with the objectives of learning Indonesian Language and Literature, namely to improve students' ability to communicate both orally and in writing and to obtain various accurate information. This study aims to determine the improvement in learning outcomes in reading news texts in grade XI MIPA 5 students of SMA Negeri 3 Bone, totaling 37 students through the application of the STAD (Student Teams Achievement Division) method. This type of research is classroom action research (PTK) or classroom action research. Data collection techniques used through observation, interviews, tests and documentation. The data obtained are then analyzed, the data used in this study is qualitative and quantitative descriptive data analysis techniques. Process data is analyzed qualitatively and student test result data is analyzed quantitatively. The results of the study indicate that through the application of the STAD method, it can improve the efficient learning process in learning to improve news text reading skills in grade XI MIPA 5 students of SMA Negeri 3 Bone.